-4(x-4) = 6x + 36
-4x + 16 = 6x + 36
-20 = 10x
x = -2
2007-04-18 13:14:25
·
answer #1
·
answered by ong_joce 2
·
1⤊
0⤋
-4(x - 4) = 6x + 36?
-4x + 16 = 6x + 36
-10x + 16 = 36
-10x = 20
x = 20/-10
x = -2
2007-04-18 20:19:04
·
answer #2
·
answered by Lost Poet 6
·
0⤊
0⤋
Simple algebra.
1) Expand the brackets:
-4x + 16 = 6x + 36
2) Gather all the x terms to one side and the units to the other.
-4x - 6x = 36 - 16
-10x = 20
3) Solve for x
x = 20/(-10) = -2
2007-04-18 20:19:20
·
answer #3
·
answered by Marco 2
·
0⤊
0⤋
Step One - Distribute = -4x+16=6x+36
Step Two - Get variables on one side = -4x - 6x + 16 =36
Step Three - Combine like terms = -10x + 16 = 36
Step Four - Isolate Variable = -10x = 20
Step Five - Solve for x :: X= -2
2007-04-18 20:16:43
·
answer #4
·
answered by x_shattered_star_drops_x 2
·
1⤊
0⤋
Whoah, deja vu. I take it you want this solved for x.
-4(x - 4) = 6x + 36
-4x + 16 = 6x + 36 *
16 = 10x + 36
-20 = 10x
x = -20/10 = -2
* - some people who are getting "5.2" are doing this step wrong.
2007-04-18 20:16:02
·
answer #5
·
answered by Anonymous
·
1⤊
1⤋
-4x + 16 = 6x + 36
-4x = 6x + 20
-10x = 20
x = -2
2007-04-18 20:15:04
·
answer #6
·
answered by richardwptljc 6
·
1⤊
0⤋
-4(x-4) = 6x + 36
-4x -16 = 6x +36
-10x =36+16
10x = -52
x = -5.2
2007-04-18 20:18:20
·
answer #7
·
answered by Nikty Pampy 1
·
0⤊
1⤋
-4x + 16 = 6x + 36
16 - 36 = 6x + 4x
-20 = 10 x
-2 = x
x = -2
2007-04-18 20:16:26
·
answer #8
·
answered by ♥vyov♥ 2
·
0⤊
0⤋
-4(x-4) = 6x +36
Distribute
-4x + 16 = 6x +36
X's alone
-4x - 6x + 16 - 16 = 6x - 6x +36 - 16
Simlify
-10x = 20
Divide
(-10x)/-10 = 20/-10
And
x = -2
2007-04-18 20:16:06
·
answer #9
·
answered by I have 0 characters to work with 3
·
0⤊
0⤋
1) -4(x - 4) = 6x + 36
Simplify and solve.
2) -4x + 16 = 6x + 36
3) -10x = 20
4) (divide by -10) x = -2
hope it helped!
2007-04-18 20:16:42
·
answer #10
·
answered by .:Tiffany:. 2
·
0⤊
0⤋